Sosialisasi dan Implementasi Aplikasi Pencatatan Informasi Keuangan (SI APIK) bagi pelaku Usaha Mikro Kecil (UMK) di Desa Wonosari - Novira Sartika; Muhammad Luthfi Iznillah; Nur Anita (Asosiasi Dosen Akuntansi Indonesia, 2022)
Indonesia's business world is currently still dominated by Micro and Small Enterprises (MSE). Bengkalis Regency occupies the fourth largest position in the province of Riau with a total of 42,029 ME. Economic Census 2016 Advanced data, about 1.71 million MSEs with business entities, less than 10 percent of which record financial statements, without financial reports it is difficult to assess performance. This situation is due to the lack of knowledge and understanding of MSE actors in the financial recording. One form of government support in helping MSMEs achieve financial literacy is by launching an android application called the Financial Information Recording Application Information System (SI APIK). This service activity is carried out using the Adaptive Collaboration Management (ACM) method. In general, MSME actors really appreciate this activity, because it becomes additional knowledge and knowledge for them and can be applied in the business that is being run. The existence of this activity provides new enthusiasm for MSME actors that problems related to the Recording of Financial Transactions can be resolved easily through the SI APIK Application